Biomarkers upon discontinuation of renal replacement therapy predict 60‐day survival and renal recovery in critically ill patients with acute kidney injury. Issue 1 (11th January 2017) - Yang, Tingting; Sun, Si; Zhao, Yuliang; Liu, Qiang; Han, Mei; Lin, Liping; Su, Baihai; Huang, Songmin; Yang, Lichuan
Abstract: Introduction: There is no consensus on the specific indications for weaning critically ill patients with acute kidney injury (AKI) off renal replacement therapy (RRT). This study aimed to explore the prognostic value of several biomarkers measured upon discontinuation of RRT for their value in predicting 60‐day survival and renal recovery in an effort to add knowledge to the decision‐making process regarding RRT withdrawal. Methods: We prospectively enrolled 102 patients with AKI who required RRT from the intensive care unit. Serum osteopontin (sOPN), serum interleukin 6 (sIL‐6), serum cystatin C (sCysC), sIL‐18, serum neutrophil gelatinase‐associated lipocalin and urinary IL‐18 and urinary neutrophil gelatinase‐associated lipocalin were measured upon discontinuation of RRT. Patients were followed up at 60 days for survival and renal recovery. Findings: Patients who survived showed lower levels of all serum and urinary biomarkers. Serum OPN (OR 1.029, 95% CI 1.013–1.047, P = 0.001), diabetes (OR 23.157, 95% CI 4.507–118.981, P < 0.001) and APACHE II score (OR 1.308, 95% CI 1.121–1.527, P = 0.001) were independent predictors of 60‐day mortality. Patients whose sOPN values fell within the highest and middle tertiles showed 5.25‐ and 2.31‐fold increased risks of mortality, respectively, compared with that of patients in the lowest tertile. The addition of sOPN to the clinical model resulted in significant net reclassification improvement of 0.453 (P = 0.026) and an integrated discriminative index of 0.155 (P = 0.032). Lower levels of sOPN and sIL‐6 were associated with greater odds of 60‐day survival (AUC 0.812 and 0.741). The AUC value for predicting survival reached its highest level when all biomarkers were combined with urine output (UO) and urinary and serum creatinine upon discontinuation of RRT (0.882). Lower sCysC performed as well as higher UO in predicting 60‐day renal recovery with the greatest AUC of 0.743. Discussion: Upon discontinuation of RRT, serum and urinary biomarkers, particularly sOPN, may predict 60‐day survival and renal recovery in critically ill patients with AKI. The serum levels of OPN, IL‐6 and CysC may be useful when considering withdrawal of RRT on the basis of conventional indicators.